Acute kidney injury in critically ill cancer patients: an update. Issue 1 (December 2016) - Lameire, Norbert; Vanholder, Raymond; Van Biesen, Wim; Benoit, Dominique
Abstract Patients with cancer represent a growing group among actual ICU admissions (up to 20 %). Due to their increased susceptibility to infectious and noninfectious complications related to the underlying cancer itself or its treatment, these patients frequently develop acute kidney injury (AKI). A wide variety of definitions for AKI are still used in the cancer literature, despite existing guidelines on definitions and staging of AKI. Alternative diagnostic investigations such as Cystatin C and urinary biomarkers are discussed briefly. This review summarizes the literature between 2010 and 2015 on epidemiology and prognosis of AKI in this population. Overall, the causes of AKI in the setting of malignancy are similar to those in other clinical settings, including preexisting chronic kidney disease. In addition, nephrotoxicity induced by the anticancer treatments including the more recently introduced targeted therapies is increasingly observed. However, data are sometimes difficult to interpret because they are often presented from the oncological rather than from the nephrological point of view. Because the development of the acute tumor lysis syndrome is one of the major causes of AKI in patients with a high tumor burden or a high cell turnover, the diagnosis, risk factors, and preventive measures of the syndrome will be discussed. Finally, we will briefly discuss renal replacement therapy modalities and the emergence of chronic kidney disease in the growing subgroup of critically ill post-AKI survivors.